Burden of intestinal parasites among diabetic patients in Africa: a systematic review and meta-analysis - Marye Nigatie Debash; Getinet Kumie; Assefa Sisay; Solomon Gedfie; Wagaw Abebe; Agenagnew Ashagre; Tadesse Misganaw; Habtu Debash; Melese Abate Reta (BMC Infectious Diseases)
Abstract Background Intestinal parasite infections remain a serious public health concern around the world, particularly in countries with inadequate sanitation. The study aims to ascertain the total magnitude of intestinal parasites in diabetes patients throughout the African countries. Objective The aim of this systematic review and meta-analysis was to determine the general burden of intestinal parasites among diabetic patients in Africa. Methods A systematic search was performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses protocol for studies reporting intestinal parasite infections in patients with diabetes through January 01/2000 to August13/2024. The collected data were analyzed using STATA software version 17. Seven case-control studies and nine cross-sectional studies were included in this study. Heterogeneity across studies was assessed using Cochran’s Q statistic and I2 statistics. Subgroup analysis was carried out when the I2 value exceeded 50%, indicating substantial heterogeneity. Results In the current systematic review and meta-analysis, the pooled prevalence of intestinal parasites in diabetic patients was 31% (95% CI: 23–38%) with heterogeneity of I2 = 95.94%; P < 0.001. The highest prevalence based on geographical area was in region of the Egypt 39% (95% CI: 26–52%), and based on study design was in case control studies 40% (95% CI: 28-52%). Poor hygiene and sanitation(P < 0.001), as well as diabetes mellitus status (P < 0.001), were statistically significant factors associated with patients who have diabetes. Conclusion Patients with diabetes are a high-risk group for intestinal parasitic infections and should be prioritized for screening. Therefore, it is essential to implement preventative measures for these patients.